Pengaruh Modal, Tingkat Pendidikan, Lama Usaha, Dan Tempat Usaha Terhadap Pendapatan Pedagang Kaki Lima Di Kecamatan Denpasar Selatan - Ni Putu Ferryka Febiola; Ni Nyoman Yuliarmi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the effect of capital, education level, business duration, and business location on the income of street vendors in South Denpasar District. The background of this research is based on the important role of the informal sector in the urban economy, particularly in creating employment opportunities and providing goods and services at affordable prices. Street vendors in South Denpasar are spread across various strategic locations with high economic activity, making it important to examine the factors influencing their income. This study employs a quantitative approach with a causal associative design. The data used are primary data collected through questionnaires distributed to street vendors. Data analysis is conducted using multiple linear regression to measure the effect of independent variables on income, both partially and simultaneously. The results show that capital, education level, business duration, and business location have a positive and significant effect on vendors’ income. This means that greater capital, higher education, longer business experience, and more strategic business locations lead to higher income. These findings highlight the importance of support in terms of access to capital, improvement in human resource quality, and proper business location arrangement. The results are expected to serve as a consideration for local governments in formulating policies to empower the informal sector, improve vendors’ welfare, and promote local economic growth.